Expanding the calibration range of compound‐specific chlorine isotope analysis by the preparation of a 37Cl‐enriched tetrachloroethylene. (2nd September 2022) - Buchner, Daniel; Martin, Philipp R.; Scheckenbach, Johannes; Kümmel, Steffen; Gelman, Faina; Haderlein, Stefan B.
Abstract : Rationale: The recent development of reliable GC/qMS methods for δ 37 Cl compound‐specific stable isotope analysis (CSIA) paves the way for dual carbon–chlorine isotope analysis of chlorinated ethenes and thus allows deeper insights into underlying transformation processes/mechanisms. A two‐point calibration is indispensable for the precise and correct conversion of raw data to the international δ 37 ClSMOC scale. The currently available calibration standards for tetrachloroethylene (PCE) span only a very narrow range from −2.52‰ (EIL2) to +0.29‰ (EIL1), which is considerably smaller than observed δ 37 Cl isotope enrichment in (bio‐)transformation studies (up to 12‰). Methods: We describe the preparation and evaluation of a new 37 Cl‐enriched PCE standard to avoid bias in δ 37 Cl CSIA arising from extrapolation beyond the calibration range. The preparation comprised: (i) partial PCE reduction by zero‐valent zinc in a system of PCE, ethanol (initial volume ratio 3/5) and trace amounts of water followed by (ii) liquid–liquid extraction and (iii) a subsequent fractional distillation to purify the 37 Cl‐enriched PCE. Results: The obtained PCE (PCEenriched ) showed a purity of 98.8% (mole fraction) and a δ 37 ClSMOC value of +10.8 ± 0.5‰. The evaluation of an experimental dataset with and without extrapolation showed no significant variation. Conclusions: The new PCE standard (PCEenriched ) expands the calibration range to 13.3‰ (previously 2.8‰) and thus prevents potential bias introduced by extrapolation beyond the calibration range.